FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEUNTUNGAN USAHATANI KAKAO DI SULAWESI TENGGARA - SAHARA, DEWI; -, DAHYA; SYAM, AMIRUDDIN (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Cocoa is Southeast Sulawesi’s prime commodity which has area about 127.547,02 ha. Kolaka regency is the central of cocoa development which contributed 73,39 % with farmer involved about 101.062 head of family. This commodity is to be source of main farmer income and regional income, so to know value income of cocoa farming system, it was done analysis to the factors which influenced profit level. The research was survey method on November – December 2004 in Pinanggosi and Aladadio villages, Lambadia sub district, Kolaka regency. The result showed that farmer income can be increased through extensification and increasing the use of fertilizer. The average of area property was 2,69 ha and fertilizer used by farmer was still under recommendation. Therefore, cocoa farming system in this research area hasn’t given the maximal profit for farmers yet.
Keywords: Cocoa Farming System, Profit, Production Factors